Details of the east-facing Mandapa of the Mahanaleshwar Temple walls - Temples of India Project Team (Jio Institute, 2024)
Seen here are the details of the east-facing mandapa (pillared hall) of the Mahanaleshwar Temple walls. The walls of the mandapa that are connected to the mukhamandapa (front porch) have jalavatayanas (perforated windows). The north and south sides of the mandapa have lateral transepts with dwarf walls. Kakshasana (seat backs) runs all along the transepts of the mandapa. This kakshasana has dwarf pillars on its corners. Just below the pillars are niches containing images of deities. The east-facing mandapa walls have images of dikapala (gods of the cardinal directions) and river goddesses.